Granular sludge-based partial denitrification/anammox achieving high anammox contribution for nitrogen removal from municipal wastewater using anoxic/aerobic process with independent sludge system - Ruixin Wu; Shenghao Ji; Chihao Lin; Haojie Qin; Min Ye; Yu-You Li; Jianyong Liu (Journal of Cleaner Production, 2026)

A novel mainstream partial nitritation process by ex-situ high salinity NOB inhibition: long-term stability and microbial response - Chihao Lin; Yanxu Liu; Yu-You Li; Jianyong Liu (Journal of Environmental Management, 2025)

Optimization of sludge retention time for rapid start-up and stable operation of high-rate partial nitritation in a continuous flow reactor treating municipal wastewater - Ruolan Wen; Min Ye; Yanxu Liu; Chihao Lin; Yu-You Li; Jianyong Liu (Journal of Environmental Management, 2025)

Pure water and resource recovery from municipal wastewater using high-rate activated sludge, reverse osmosis, and mainstream anammox: A pilot scale study - Haoran Zhao; Yu Zhou; Lianpei Zou; Chihao Lin; Jianyong Liu; Yu-You Li (Water Research, 2024)

Research on Hydrodynamics of Trans-Media Vehicles Considering Underwater Time-Varying Attitudes - Shuo Liu; Chihao Du; Yijie Han; Yu Zhang; Wanglin Lin; Yong Cai; Tao Wang (Journal of Marine Science and Engineering, 2024)
A trans-media vehicle is a new type of equipment that can adapt to two environments, water and air, to maintain optimal hydrodynamic and aerodynamic performance. However, no matter what kind of trans-media vehicle, its dynamics are much more complicated when traversing the interface of the medium, as the parameters are time-varying due to the change in ambient medium and vehicle attitudes. In order to improve the stability and performance of the trans-media vehicle in complex environments, an accurate mathematical model is established to characterize the dynamics of the trans-media vehicle in this process in this study. The time-varying hydrodynamic coefficients with different attitudes or depths are obtained using computational fluid dynamics software. The mathematical model is solved iteratively using a Runge–Kutta solver to calculate the dynamic response. A prototype of trans-media vehicle is fabricated, and motion experiments are performed in the pool. The experimental results confirm the effectiveness of the established model and lay the foundation for further controller design, providing a reference for the dynamic modeling of other similar equipment operating in complex environments. The primary novelty of this study lies in the fact that the established dynamic model considers the complex interaction between the attitude of the trans-media vehicle and the inherent different properties of water and air and utilizes computational fluid dynamics software to accurately obtain time-varying coefficients under different attitudes and depths. This approach not only recognizes the criticality of orientation-dependent hydrodynamic coefficients but also incorporates their temporal variations, which were often overlooked in previous studies.

Assigning strategic COD flow to enhance denitrification coupled with anaerobic digestion and anammox for systematic upgradation of advanced nitrogen removal from food waste digestate - Jie Tan; Min Ye; Chihao Lin; Bohan Yu; Yu-You Li; Jianyong Liu (Chemical Engineering Journal, 2024)

Achieving rapid start-up of mainstream partial nitritation by sludge treatment using high salinity - Chihao Lin; Yanxu Liu; Yu-You Li; Jianyong Liu (Chemical Engineering Journal, 2024)

Difference of high-salinity-induced inhibition of ammonia-oxidising bacteria and nitrite-oxidising bacteria and its applications - Chihao Lin; Yanxu Liu; Yu-You Li; Jianyong Liu (Bioresource Technology, 2023)

Simvastatin-enhanced bioinspired exosome mimetics regulate osteogenesis and angiogenesis for the treatment of glucocorticoid-induced osteonecrosis of the femoral head - Hongyi Jiang; Chao Lou; Liting Jiang; Chihao Lin; Weidan Wang; Zijian Yan; Jiachen Yu; Tingwen Cai; Shida Lin; Jilong Wang; Xiaoyun Pan; Xinghe Xue (Chemical Engineering Journal, 2023)

Construction and comprehensive analysis of a lncRNA–mRNA interactive network to reveal a potential lncRNA for hepatic encephalopathy development - Chihao Zhang; Wei Ni; Yiming Zhu; Jiayun Lin; Hongjie Li; Zhifeng Zhao; Ke Wang; Haizhong Huo; Meng Luo (Human Cell, 2022)

Improved forward and backward adaptive smoothing algorithm - Xu Lin; Xinghai Yang; Chihao Hu; Wei Li (GPS Solutions, 2022)

Street-block collapsed buildings assessment: A case study of Banqiao District, New Taipei City - ITien Lo; ChingYuan Lin; ChengTao Yang; YingJi Chuang; ChiHao Lin (Earth Science Informatics, 2021)